Young Women Subjected to Nonconsensual Condom Removal: Prevalence, Risk Factors, and Sexual Self-Perceptions - Boadle, Allira (Violence against women, 2021)
The purpose of this study was to investigate nonconsensual condom removal (NCCR), also termed “stealthing,” which involves a male partner removing a condom during sex without knowledge or consent. Young women (N = 364) provided self-report data on sociodemographic characteristics, NCCR experiences, and sexual self-perceptions. Almost 10% of the participants reported experiencing NCCR, with increased risk linked to nonheterosexuality, nonexclusive relationship status, and more sexual partners. Women with NCCR histories reported less confidence to refuse unwanted sexual advances and felt less in control of themselves as sexual beings. Together, the findings suggested NCCR is a somewhat common sexual risk behavior which may pose acute and sustained psychosexual harm to victims.